Enhancing Hypertension Management Through Audiovisual Self-Management Tools - Mukhlis Solehin, Muhammad; Yulyanti, Yulyanti; Aufa, Naimatun; Negara, Candra Kusuma (Jurnal EduHealth, 2024)
Introduction: Hypertension, also known as high blood pressure, is a condition where the blood pressure of an individual exceeds normal limits, posing risks such as pain and even death. Self-management of hypertension is crucial to control and manage symptoms, minimize disruptions to bodily functions and emotions, prevent complications, and achieve optimal health. Method: This study employed the Research and Development (R&D) method. The R&D method is used to develop and validate products or processes, including testing the effectiveness of existing products. Validation tests were conducted by three expert nurses and health promotion specialists, with limited testing carried out on 10 respondents. Results: Based on the recapitulation of validation tests and limited trials, the results indicate that audiovisual media for self-management of hypertension received a very favorable rating. Discussion: This study demonstrates that audiovisual self-management tools for hypertension are highly suitable as educational aids in health promotion processes.